KIE (KOMUNIKASI, INFORMASI DAN EDUKASI) TENTANG GIZI IBU HAMIL - Dwi Pratiwi Kasmara; Reni Yusman; Tika Kecana; Susilawati Br Sembiring; Ernawati Sembiring (Jurusan Kebidanan Poltekkes Kemenkes Riau, 2023)
Nutrition is one of the factors that influence the success of a pregnancy. Even the nutritional status of pregnant women can affect the birth weight of the baby and is very closely related to the next level of infant health and infant mortality. Pregnant women need more nutrients compared to non-pregnant women. This is because in addition to the mother, nutrients are needed for the fetus. The fetus grows by taking nutrients from the food consumed by the mother and from the stores of nutrients in the mother's body. During pregnancy a mother must increase the amount and type of food eaten to meet the needs of the baby's growth and the needs of mothers who are carrying a baby and to produce breast milk. The community service was carried out at the Independent Practice Midwife Ernawati Sembiring in the Langkat district, North Sumatra province, with 35 people. The results of the implementation of community service activities carried out in January 2023 at Ernawati Sembiring's Independent Practice Midwife (BPM) obtained an average value of knowledge of pregnant women about Nutrition for Pregnant Women) before and after the Communication of Information and Education (IEC) was carried out, namely from the average value 35 to an average of 85. This can be seen from the results of filling out questionnaires by pregnant women who were carried out before and after the activity. This increase in knowledge is because pregnant women have received KIE material (Communication, Information and Education) on Pregnant Mother Nutrition. Keywords: Nutrition for Pregnant Women, KIE, Pregnant Women